Assessment of the effectiveness of the fisheries code for fish stock management in the coastal barangays of Panabo City - Cortel, Imme A. (UP Mindanao, 2006)
The objective of this study was to assess the effectiveness of the Fisheries Code in fish stock management in selected coastal barangays of Panabo City. Specifically, the study evaluated the status of fish stock, assessed the living condition of municipal fishers in the area, evaluated the level of awareness about and acceptability of the Fisheries Code among municipal fishers, and identified factors that could affect compliance with the policy. Primary data were gathered through interviews with municipal fishers from barangays San Pedro, Cagangohan, and J.P. Laurel. Results of the study show that policy awareness, acceptance and compliance were high for all three barangays. Fish stock improvement was perceived by majority of the respondents from barangay Cagangohan, where increase in fish catch was also noted. Respondents from barangays J.P. Laurel and San Pedro believed that there was no improvement in the status of fish stock because of the worsening water pollution. However, majority of the respondents from all three barangays believed that there had been an improvement in the enforcement of the law. Based on the results of this study it can be concluded that policy awareness affects policy acceptance and compliance. At the same time, strengthened policy enforcement contributed by policy compliance. Fish stock management was also found to be greatly affected by the financial status of municipal fishers, population of municipal fishers and the coastal communities an water pollution.